Estabilidade da cor da madeira de Tauari (Couratari sp.) modificada termicamente submetida ao intemperismo natural - Ferreira, Jessica Sabrina da Silva (2024)
The general objective of this work was to evaluate the effect of thermal modification on the colorimetric stability of tauari wood (Couratari sp.) subjected to natural weathering in the Brazilian Amazon region. Thermally modified wood (TMW) was produced in a laboratory facility at 180 ºC, 190 ºC, 200 ºC, and 210 ºC, in addition to the untreated wood. The wood was exposed to natural weathering in the city of Santarém, Pará, from January 2022 to January 2023. Colorimetric analyses of the wood were carried out using the CIELab color space, as well as the moisture content (gravimetric method) and the surface chemical composition (near-infrared spectroscopy – NIRS). For these analyses, the following periods were considered: before the natural weathering test and after 1, 2, 3, 6, 9, and 12 months of testing. All color parameters (L*, a*, and b*) varied throughout exposure to weathering, however the effect was smaller in TMW. Regardless of the original color, the wood of all treatments acquired gray tones within the first few months of testing. TMW at higher temperatures had lower moisture content (200 ºC and 210 ºC), and greater stability, both colorimetric (200 ºC and 210 ºC) and chemical (190 ºC and 210 ºC) throughout the weathering test when compared to the untreated wood.